2016
DOI: 10.1158/1078-0432.ccr-15-2518
|View full text |Cite
|
Sign up to set email alerts
|

VEGF Potentiates GD3-Mediated Immunosuppression by Human Ovarian Cancer Cells

Abstract: Purpose Natural killer T (NKT) cells are important mediators of anti-tumor immune responses. We have previously shown that ovarian cancers shed the ganglioside GD3, which inhibits NKT cell activation. Ovarian cancers also secrete high levels of vascular endothelial growth factor (VEGF). In this study, we sought to test the hypothesis that VEGF production by ovarian cancers suppresses NKT cell-mediated anti-tumor responses. Experimental Design To investigate the effects of VEGF on CD1d-mediated NKT cell activ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 54 publications
1
25
0
1
Order By: Relevance
“…Consistent with our observations that TIMP-1 significantly increased in TIF with VEGF overexpression in MCF-7 tumors, exogenous VEGF administration has been associated with TIMP-1 release in the retina40, although the regulation of TIMP-1 by VEGF is not fully understood. TIMP-1 is known to play a role in inflammation and immunity41, and its increase with VEGF overexpression is consistent with observations that VEGF potentiates immune suppression42.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with our observations that TIMP-1 significantly increased in TIF with VEGF overexpression in MCF-7 tumors, exogenous VEGF administration has been associated with TIMP-1 release in the retina40, although the regulation of TIMP-1 by VEGF is not fully understood. TIMP-1 is known to play a role in inflammation and immunity41, and its increase with VEGF overexpression is consistent with observations that VEGF potentiates immune suppression42.…”
Section: Discussionsupporting
confidence: 82%
“…Spannuth et al have demonstrated higher expression of VEGFR2 in malignant ovarian samples compared to benign or borderline tumours, which showed a correlation with tumour grade and aggressiveness3952. Moreover, VEGFA suppresses immune-mediated anti-tumour responses in EOC53. Although these findings indicate that the VEGF/VEGFR loop promotes malignant progression in EOC, the role of this pathway in driving the chemoresistant disease is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…discuss our recent findings (8) and provide insight into potential future directions. The impact of angiogenic factors on the tumor microenvironment, reported by Bamias and Gavalas, underscore the effects of VEGF on immune cell responses.…”
mentioning
confidence: 87%
“…It has been well established that evading immune surveillance is critical for tumor growth and metastasis, and other groups have shown that vascular endothelial growth factor (VEGF) expression is inversely correlated with survival in ovarian cancer patients (6,7). Therefore, we investigated the effects of ovarian cancer-associated VEGF on CD1d-mediated antigen presentation to natural killer T (NKT) cells (8). We found that inhibition of VEGF production by ovarian cancer cell lines led to a reduction in the expression of the immunosuppressive ganglioside GD3 and restored NKT cell activation.…”
mentioning
confidence: 99%